Veterinary phytotherapy in Algeria: /Pistacia lentiscus as an antimicrobial model - Djebrane, Chahinése; Belahcene, Nabiha; Boulebda, Nadji (Brazilian Journal of Veterinary Research and Animal Science, 2021)
Currently, the use of alternative medicine is necessary, even in animals. Our study focused on the valorisation of the use of herbal products in Algerian veterinary medicine. This study is based on a 6-month exploratory survey of 257 private practicing veterinarians, followed by a study of the bacteriological activity of the essential oil of the Pistacia lentiscus plant. The survey results generally  indicate that private veterinarians support phytotherapy as an alternative to conventional drugs in several areas and species. Also, the results of research conducted on the antibacterial activity of Pistacia lentiscus essential oil show that it inactivates 50% of the bacterial strains. This confirms the well defined role of this medicinal plant used as an alternative in veterinary medicine.